The Debate Strategy And Its Contribution To The Arabic Learnerâ€™s Competence/ Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠÙ‘Ø© Ø§Ù„Ù…Ù†Ø§Ø¸Ø±Ø© Ùˆ Ø§Ø³Ù‡Ø§Ù…Ù‡Ø§ Ø¹Ù„Ù‰ ÙƒÙØ§Ø¡Ø© Ø§Ù„Ù…ØªØ¹Ù„Ù‘Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Fikri, Shofil; Machmudah, Umi; Halimi, Halimi; Ibrahim, Faisal Mahmoud Adam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research is based on a lack of confidence in the success achieved by language learners in the Arab debate competition at the ASEAN level at the Islamic Science University of Malaysia 2018. Language learners in the Arab debate competition at the international level in Doha - Qatar 2018 because not everyone can master debate easily and quickly. It needs To a unique strategy, numerous practices. Therefore, this study aims to: 1) Describe the strategies used by the successful learners in a debate competition. 2) Enhancing the contribution of debate learning to the competence of the learner. In this study, the researcher used the qualitative approach and the case study. This study concludes from the following results:Â First, the strategies of successful learners in the debate competition are of two types, 1) Debate learning strategy in the form of a Strategy Inventory for Language Learning, 2) Debate strategy, which is: (1) an organization strategy, (2) a rebuilding strategy,) 3) a strategy for clarification and detail, (4) a strategy for communication, (5) an argument strategy, (6) a strategy for working within groups.Â Second, learning to debate has contributed to improving the learner's three competencies (linguistic, communicative, and cultural competency) faster simultaneously, with two main aspects: 1) acquiring materials, 2) presenting the speech